2002
DOI: 10.2174/1566524023361907
|View full text |Cite
|
Sign up to set email alerts
|

Dendritic Cells in Innate Immune Responses Against HIV

Abstract: Dendritic cells (DCs) were recently found to be innate immunity effectors against tumoral cells and viruses. (i) In response to most viruses, including HIV, plasmacytoid DCs are responsible for most of the type I IFN secretion, which is strongly anti-viral and induces TH1 type responses. Myeloid DCs secrete IL-12, which is also important for TH1-type and cytotoxic responses. In HIV patient blood, both DC population numbers decrease as early as the primary stage. Plasmacytoid DC numbers correlate with type I IF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
28
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(30 citation statements)
references
References 140 publications
(205 reference statements)
2
28
0
Order By: Relevance
“…Our findings indicate that mDC and pDC undergo spontaneous cell death during culture, supporting the hypothesis that the loss of DC may be due to cell death (39,40). Notably, the amine reactive viability dye used in this study identifies not only necrotic but also late or postapoptotic cells (41), and preliminary experiments have identified viable DC in the lymph nodes of monkeys with AIDS that are annexin Vpositive (data not shown), suggesting that the DC may be undergoing apoptosis.…”
Section: Discussionsupporting
confidence: 83%
“…Our findings indicate that mDC and pDC undergo spontaneous cell death during culture, supporting the hypothesis that the loss of DC may be due to cell death (39,40). Notably, the amine reactive viability dye used in this study identifies not only necrotic but also late or postapoptotic cells (41), and preliminary experiments have identified viable DC in the lymph nodes of monkeys with AIDS that are annexin Vpositive (data not shown), suggesting that the DC may be undergoing apoptosis.…”
Section: Discussionsupporting
confidence: 83%
“…We found that HIV-1 induced TRAIL and IFN-␣ production by monocytes, which may contribute to the high levels of both cytokines in patients (10), despite the reported reduction of blood pDCs in progressive HIV-1 disease (17,30). This reduction of circulating pDCs may be due to their redistribution to lymphoid tissue (31), which could result in IFN production, leading to TRAIL expression by CD4 ϩ T cells and apoptosis of DR5 ϩ CD4 ϩ T cells (11). This hypothesis is consistent with our finding that HIV-1 induced TRAIL production in ex vivo tonsil cultures (10).…”
Section: Discussionmentioning
confidence: 66%
“…DCs may play a central role in MV-associated immunosuppression. One suggested mechanism is TRAIL-mediated apoptosis of T cells (42). However, TRAIL was similarly induced by all pathogens and therefore is not a unique mechanism for immunosuppression in measles.…”
Section: Discussionmentioning
confidence: 99%